La fundación de la Academia Francesa - Víquez Ruiz, Marcos (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2015)
Este artículo presenta la información más importante de la fundación de la Academia Francesa (1635). Comienza con el legado de "Akadernos", en cuyos jardines Platón hablaba sobre filosofía. Continúa con la contribución del Renacimiento Italiano, particularmente del "Hotel de Rarnbouillet", el aposento literario privado de la Marquesa de Rarnbouillet. Finalmente, se enfatiza la participación de los precursores de la fundación de la Academia: el Cardinal de Richelieu, el estudiante Valentin Conrart, en cuya casa se reunió un círculo de escritores y hombres de letras, progenitores de la idea de la Academia, Boisrobert, Cerisay, Desmarets, Faret, Godeau, Gombauld, Malleville, el abad de Serisy y Vaugelas. This article presents the most relevant information on the establishment of the French Academy (1635). It begins with the legacy of Akadmus, in whose gardens Plato exposed his philosophy, as well as with the contribution of Renaissaance Italy and particularly of "Hotel de Rambouillet", the private literary room of Marquise de Rambouillet. Finally, the article highlights the participation of the direct forerunners of the establishment of the Academy: Cardinal de Richelieu, the scholar Valentin Conrart, whose house served as a gathering place for a circle of writers and men of letters from whose minds arose the idea of this establishment, Boisrobert, Cerisay, Desmarets, Faret, Giry, Godeau, Gombauld, Malleville, the abbot of Serisy and Vaugelas.